Technical and experimental errors in the spectrophotometric determination of oxygen saturation - Fish, R. G. (1963)
The method of Deibler, Holmes, Campbell, and Gans (1959) is a quick, accurate, and reliable method for the determination of oxygen saturation. The results should be calibrated against those obtained by the Van Slyke method, and the setting, sensitivity, and reliability of the spectrophotometer should be carefully established. This is especially necessary to meet the stringent requirements for accurate setting at the isobestic point 805 mμ. This method is superior to a method using saponin as a haemolytic agent and reading at only one wavelength.